The Performance of Forestry Human Resources in Licensing Forest Utilization, The Lease of Forest Area, and The Release of Forest Area - Nurtjahjawilasa Nurtjahjawilasa; Hariadi Kartodihardjo; Dodik Ridho Nurrochmat; Agus Justianto (Institut Pertanian Bogor (IPB University), 2015)
Performance assesment includes the quantity and quality measurements of individual or group works within organization in carrying out duties and functions. It is based on norms, standard operational procedure (SOP), and specified criteria in an organization. Factors affecting quality and quantity of individual performance in an organization are skills, experience, ability, competence, willingness, energy, technology, leadership, compensation, clarity of purpose, and security. This study aims to identify and analyze the performance of forestry human resources (HR) related to licensing forest utilization, releasing forest area, and leasing forest area. The results of the study are: (1) the performance of forestry HR in licensing forest utilization was relatively still poor; (2) the structure (rules, norms, cultural cognitive) of forestry HR was unclear and is not well developed; and (3) the culture of learning organization, including personal mastery, mental models, shared vision, team learning, and system thinking is still insufficient and needs to be developed at the ministerial, provincial, and district/city levels. Some suggestions for improving the performance of forestry HR are: (1) establishing an appraisal team/task force of forestry HR performance; (2) developing commitment for high quality service at the bureaucratic elites and their highest level networks; and (3) considering the development of one stop licensing supported by online system to promote transparency and public accountability.